Treatment patterns and real-world clinical outcomes in patients with advanced endometrial cancer that are non-microsatellite instability high (non-MSI-high) or mismatch repair proficient (pMMR) in the United States - Sneha S. Kelkar; Vimalanand S. Prabhu; Jingchuan Zhang; Shelby Corman; Cynthia Macahilig; Nifasha Rusibamayila; Shardul Odak; Linda R. Duska (Gynecologic Oncology Reports, 2022)
Objective: Microsatellite instability (MSI) due to defective DNA mismatch repair has emerged as an actionable biomarker in advanced endometrial cancer (aEC). Currently, there are no treatment patterns and outcomes data in non-MSI-high (non-MSI-H) or mismatch repair proficient (pMMR) aEC patients following prior systemic therapy (FPST). Our goal was to describe real-world data in this population in the US in 2019 and prior years. Methods: Endometrial Cancer Health Outcomes (ECHO) is a retrospective patient chart review study conducted in the US. Patients with non-MSI-H/pMMR aEC and progression between 06/01/2016–06/30/2019 FPST were eligible. Data collected included patient demographics, clinical and treatment characteristics, and clinical outcomes. Kaplan-Meier analyses were performed to estimate time to treatment discontinuation, real-world progression-free survival (rwPFS), and overall survival (OS), separately by treatment category. Results: A total of 165 eligible patients initiated second-line therapy with chemotherapy ± bevacizumab (n = 140) or hormonal therapy (n = 25). Median age was 66.0 years at aEC diagnosis, 70.2% were Stage IIIB-IV, 40.0% had ECOG ≥ 2 at second-line therapy initiation. Median rwPFS was 5.0 months (95% CI: 4.0–6.0) for patients receiving chemotherapy ± bevacizumab and 5.5 months (95% CI: 3.0–29.0) for those receiving hormonal therapy. Median OS was 10.0 months (95% CI: 8.0–13.0) and 9.0 months (95% CI: 6.0-NA) in these groups, respectively. Conclusions: Non-MSI-H/pMMR patients who initiated second-line therapy with chemotherapy ± bevacizumab or hormonal therapy had poor clinical outcomes with a median survival less than 1 year and rwPFS less than 6 months. This was the first study to define the clinical unmet need in patients with non-MSI-H/pMMR aEC with conventional therapy.